A Theory of the Start-Up Workforce - Bort, James (Academy of Management Review, 2026)
Start-up employees are a crucial yet understudied stakeholder group. This paper develops a theory of the start-up workforce that positions early-stage employees as influential co-constructors of entrepreneurial opportunities. Drawing on constructivist logic and integrating insights from entrepreneurship and organizational behavior, I explore how entrepreneurial opportunity narratives and career fit narratives, generated at the firm and start-up employee levels, respectively, interact and evolve over time. My model unpacks how narrative fidelity—the completeness and coherence of a story—changes across levels as start-ups take shape. Low-fidelity entrepreneurial opportunity narratives attract employees by allowing them to envision themselves as co-constructors. However, narratives solidify as fidelity increases through employment growth and employee entrainment. This process then influences employees’ career fit narratives and their decisions to maintain entrainment or resist and exit. By illuminating the dynamic interplay between macro-level entrepreneurial opportunities and micro-level employee career fit, this interdisciplinary theory advances our understanding of why and when start-up employees entrain or resist, and how their co-constructive efforts significantly influence both the respective start-up’s trajectory and their career fit narrative revisions. My work provides tractable theoretical foundations to further distinguish the start-up workforce as a unique stakeholder group within new ventures facing a novel employment situation.